The Enduring Ambiguities of Japan's Postwar Secularism - Rangdrol, David (Université d'Ottawa / University of Ottawa, 2018)
Following decades of state control of religion, a secular constitution was introduced in Japan in 1947, presenting favourable prospects for safeguarding freedom of conscience and equality. However, the vague language used in Articles 20 and 89 of the constitution arguably complicated the task of creating a strong, liberal secular regime. This thesis, therefore, will describe how institutional flaws have compounded the secularism-related challenges linked to the revival of Shinto’s public role in the postwar era, as well as the controversies surrounding the creation of a powerful Buddhism-based political party, the Komeito. In this regard, the Japanese case provides an opportunity to reflect on similar issues elsewhere in the world. Indeed, attempts at fostering citizens’ civic cohesion are being challenged in nation-states worldwide; on one hand, by the absolutist goals of religio-political movements, and on the other, by state-led constructions of national and religious identities. The Japanese case can especially contribute to the debates concerning the introduction of secularism in non-Western societies – notably where the notions used to articulate secularism, such as the religion–state dichotomy, either are absent or lack deep cultural and historical roots. By focusing on the impact of key ambiguities found at the core of Japan’s secular rules, the thesis will argue that institutional design choices, rather than cultural barriers, are responsible for some of the most important challenges confronting secularism in Japan today.
Keywords: Secularism; Japan; Institutionalism; State Shinto; Komeito; Soka Gakkai